Analysis of Learning of the Quran Based on Tahsin, Tartil, and Tilawah Methods in TPQ Al-Muttaqin Kunir - Azizah, Hafidzotul (Proceeding International Conference on Religion, Science and Education, 2022)
The purpose of this study was to find out more about how the implementation of learning the Qur'an at the Al-Qur'an Al-Muttaqin Education Park in Kunir Village. Tpq Al-Muttaqin is an informal Islamic educational institution that conducts learning of the Qur'an by emphasizing its students on the learning process of tahsin, tartil and recitations. The research method used is descriptive qualitative analysis. The data analysis technique used is triangulation based on data reduction, data presentation, and drawing conclusions. Data collection techniques used are interviews, documents, and documentation. The results of this study indicate that (1) TPQ Al-Muttaqin Kunir village is able to produce a generation of students who are good at tahsin, tartil and recitations with individual classical methods and sorogan, In addition to learning the Qur'an, it also teaches students various daily practices in the form of prayer, prayer, remembrance, and shalawat by making students have goals based on Islamic guidelines, and making people who have good morals and virtues. 2) The supporting factors for learning the Koran based on the tahsin, tartil, and recitation methods at TPQ are the commitment of teachers who teach sincerely, the attitude of discipline and teacher responsibility in carrying out their teaching tasks, the assistance for Koran education activities at TPQ, and the existence of adequate facilities and infrastructure in the process of learning the Koran. (3) the inhibiting factor: students study only in the TQQ place by not repeating the reading of the Koran at their respective homes.